The working-class struggle against capitalist oppression in Aravind Adiga’s The White Tiger - Trianingtyas, Aprilia; Anam, Zuhrul (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
In a capitalist society, there are two classes based on ownership of the means of production: the working class and the capitalist class. However, the emergence of this stratification sometimes leads to large disparities and differences in interests between classes that lead to oppression by the upper class and resistance from the lower class. Aravind Adiga's The White Tiger depicts class struggle as a form of lower-class resistance to upper-class oppression in India. The purpose of this study is to identify the forms of oppression of the capitalist class and explain how the working class conducts class struggle against the oppression. The method used is a qualitative study and analyzed using Marxist theory by Karl Marx. The White Tiger indicates that oppression occurs because of the capitalist class' desire to maintain its power and status quo. The working class are depicted as the party that is always disadvantaged. Eventually, this triggers resistance in the form of class struggle by the working class. Adiga seems to convey that the power and injustice of the capitalist class is a cause for resistance because it tends to harm the working class.